Anti-Leptospira spp. antibodies in wild mammals in the municipality of Monte Mor, São Paulo State, Brazil - Cutolo, André Antonio [UNESP]; Wanderley, Guido Gomes; Langoni, Helio [UNESP]; Teixeira, Carlos Roberto [UNESP] (Universidade Estadual de Londrina, 2020)
Leptospirosis is a potentially fatal zoonosis caused by Leptospira bacteria. Some animal host species are adapted to specific serovars being potential carriers and environmental dispersers. From 2009 to 2011, 45 wild mammals (39 opossums Didelphis albiventris, four porcupines Sphiggurus villosus, one coypu Myocastor coypus and one capybara Hidrochoerus hidrochaeris) found by citizens in anthropic areas of Monte Mor municipality were captured, restrained and had sera samples collected for Leptospira antibody detection. The samples were titrated by the microagglutination technique (MAT) for different serogroups. A total of 35.56% (16/45) animals were reactive for Leptospira antibodies for 11 different serogroups. The most frequent serovar, among the 12 identified, was Icterohaemorrhagiae (6/16), followed by Gryppotyphosa (4/16) and Pyrogenes (2/16). Didelphis albiventris, the most abundant species in the study, had a prevalence of 35.9% (14/39) for Leptospira antibodies, while S. villosus had 0% (0/4), M. coypus (1/1) and H. hydrochaeris (1/1) 100%. Among the seropositive D. albiventris, 35.71% (5/14) and 28.57% (4/14) seroreacted for Leptospira interrogans species, serogroups Icterohaemorrhagiae and Gryppotyphosa respectively, indicating environmental contamination by these bacteria and the possibility of exposure and infection of humans and domestic animals in the studied area.
Anticorpos anti-Leptospira spp. em mamíferos silvestres do município de Monte Mor, estado de São Paulo, Brasil
Keywords: Campinas metropolitan region; Leptospirosis; Opossum; Reservoir; Serology